A new case of partial trisomy 19q (q13.2–>qter) owing to an unusual maternal translocation. Issue 8 (August 1993) - Valerio, D; Lavorgna, F; Scalona, M; Conte, A
Abstract : A new case of trisomy 19q13.2–>qter is described in a male child which was caused by a maternal balanced translocation (13;19)(p13;q13.2). The major clinical features detected in the patient included the following: facial dysmorphism, bilateral coloboma, narrow and hypoplastic nails, cardiac malformations (Fallot's tetralogy), genitourinary and gastrointestinal anomalies, and agenesis of the corpus callosum. A comparison with other reported cases of partial trisomy 19q is presented. A hypothesis is proposed to account for the involvement of p13 regions of different acrocentrics in some cases of familial translocations involving a chromosome 19.